The Use of Meaningful Learning in Distance Learning - Lestari, Nita; Murni Winarsih; Dwi Kusumawardani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
This article aims to evaluate meaningful learning strategies in distance education. The application of meaningful learning is the emphasis of this class action research project with 32 respondents from class XI, in the application of meaningful Education using the principles of an advance organizer, progressive differentiation, integrative reconciliation, and consolidation in each learning activity. This study is classroom action research (CAR) conducted in two cycles. Data collection consisted of two research cycles: student activity data and student learning outcomes data. Student activity data was collected using observation sheets, while student achievement data was collected using the test method in each cycle. The criteria for grouping activities in each learning cycle use the ideal average and standard deviation. Sources of data include observations, questionnaires, and documentation for learning outcomes. The finding showed that meaningful learning model activities effectively increased student learning motivation. This can be seen from the increase in the average score of students on the test results; 67,15 in cycle 1 and 77,04 in cycle 2. The increase was also seen based on the results of the observations, which showed positive responses from students. From the results of the questionnaire, it is known that the average student perception score is 32.281 or 96%. This means that students positively respond to this learning model's application.